IDENTIFIKASI RASIO PARAMETER KAPAL PENUMPANG CATAMARAN BERBAHAN FRP - hardjono, Soegeng (Badan Pengkajian dan Penerapan Teknologi, 2010)
Parameter ratios are important information for the ship designer in the preliminary design stages. They can be used as a tool to identify the main parameter of vessel and their other technical characteristics. The information about parameter ratios of mono-hull vessel is currently available in Naval Architecture literatures, but it is not the case for the type of twin-hull vessel called catamaran. Having conducted technical analysis in this research, it has been identified that parameter ratios of passenger catamaran vessel made of FRP has values of L / B ratio from 2.52 up to 3.7, L / D ratio from 5.25 up to 11:24, slenderness ratio (Lwl/BwL) from 9 up to 12. Other values of various parameter ratios like B/T, D/T, L /√ L, and Displacement/L are also discussed.